Credit, social mentality and technical innovation efficiency - Zhou, Tingting; Hu, Dandan (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
Existing literature has confirmed the importance of science and technology innovation on its promoting sustainable, healthy and rapid growth of economy from the perspective of innovation forms, regional environment, and time phases, but the influence of social factor is neglected in the research of the efficiency of technology. Using provincial panel data during the period of 2000 to 2013, we probe into a path that improves the effects of science and technology innovation on economic growth from the perspective of social environment rather than of pure technology. This study introduces social factor into research model and takes account of credit construction and social mentality to explore the impact mechanism of science and technology innovation on economic growth. The results indicate that the regional innovation activities remarkably improve the growth of economy. The establishment of regional credit websites and the publication of honest and dishonest behavior dramatically improve the promoting effects of innovation on the economy. Positive social mentality can spread the â€œpositive energyâ€ through shared reality, inter-subjectivity consensus and social representation in the social interaction to promote the technical innovation efficiency. The higher attentions of regional netizens to stress, anxiety, indifference, anger, rich second generation, wealth showoff have negative impacts on the innovative activities and weaken the innovationsâ€™ support to economic growth. This study suggests that regional governments strengthen the process of credit construction in the aspect of formulating credit policies and regulations, standardizing the credit information platform and credit service market, and finally establishing a sound social credit system. Besides, governments need to guide positive social mentality into the mainstream ideology of the society and pay attention to online public opinions to properly channel the negative emotions that hinder the healthy development of social mentality.